Technical analysis of urban drainage problems on the street Rio Grande do Norte of Açailândia – Maranhão considering the slope of the road and its impact on water drainage in rainy periods (Research, Society and Development, 2023)
It is known that there is not always an adequate dimensioning of culverts, gutters and galleries in the drainage system of the cities, it is also possible to find the absence of the study of the soil survey, the inclination of the road or the study of the hydrographic basins present in the localities where a new road and drainage network is created, in addition, due to the urbanization system occurring in an uncontrolled way in several situations, problems of flooding also arise in different parts of the city due to the absence of adequate urban planning. Thus, a diagnosis was carried out to identify the real problem in the drainage of Rua Rio Grande do Norte in Açailândia-MA, in addition to analyzing the unevenness of the road and proposing adequate measures to remedy the difficulties of water drainage in the studied route. This article presents the results that allow decision-making to choose actions that aim to reduce or eliminate the identified problems, generating a critical eye and being able to focus on the proposed solution for flooding problems, for example.